Preparation method and application of lithium iron phosphate system fast charging type power lithium ion battery electrolyte

By using secondary liquid injection and gradient control of VC content, combined with the synergistic film-forming effect of FEC and DTD, a low-impedance SEI film was constructed, which solved the contradiction between fast charging and cycle performance of lithium iron phosphate batteries, and achieved efficient fast charging and long life performance of the battery in a wide temperature range.

CN121076262APending Publication Date: 2025-12-05HUADING GUOLIAN SICHUAN POWER BATTERY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511331096.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing lithium iron phosphate fast-charging power lithium-ion batteries suffer from a contradiction between fast charging and cycle performance. The low interfacial impedance and high interfacial stability brought by the electrolyte are difficult to balance. Furthermore, the battery has multiple kinetic bottlenecks, such as slow lithium-ion diffusion rate on the positive electrode side, easy lithium deposition on the negative electrode side during high-rate charging, and low electrolyte ion transport efficiency.

Method used

An innovative two-stage liquid injection method is adopted to rationally allocate the content of vinylene carbonate (VC) and optimize the liquid injection ratio. The SEI impedance is controlled during the cell formation stage. Through the synergistic film formation effect of FEC and DTD, a low-impedance SEI film is constructed. Combined with the LiPF6 and LiFSI compound lithium salt system, the solvent combination is optimized to form a composite SEI film to achieve dynamic repair.

Benefits of technology

It achieves a charging time of ≤19 minutes in the 10%-80% SOC range, ≥1000 cycles of 2.2C fast charging at room temperature, and ≥1300 cycles of high temperature cycling, balancing the battery's fast charging performance and high temperature cycling stability, reducing interface impedance and enhancing interface stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005601166150000161
    Figure BDA0005601166150000161
  • Figure BDA0005601166150000171
    Figure BDA0005601166150000171
  • Figure BDA0005601166150000172
    Figure BDA0005601166150000172
Patent Text Reader

Abstract

The invention relates to a preparation method of a lithium iron phosphate system fast charging type power lithium ion battery electrolyte, which is realized by a secondary liquid injection method, and comprises the following steps: S1, carrying out primary liquid injection on a battery, and using an electrolyte A which contains 0.5-1.5 wt.% of vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethylene sulfate (DTD), a solvent and a lithium salt; s2, placing and forming the battery after the first liquid injection; s3, performing secondary liquid injection on the battery, wherein additives in a used electrolyte B comprise 18-25wt% of vinylene carbonate (VC), a solvent and a lithium salt; s4, standing the battery at high temperature and normal temperature to stabilize SEI and free ions; and S5, carrying out normal-temperature capacity grading on the battery after liquid injection. The invention also relates to the secondary power battery obtained by the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and more particularly to lithium-ion battery electrolytes, especially to a method for preparing and applying a lithium iron phosphate system fast-charging power lithium-ion battery electrolyte. Background Technology

[0002] With the booming development of the new energy vehicle industry, consumers have increasingly stringent requirements for the fast charging performance of power batteries. Lithium iron phosphate (LFP) batteries have become one of the mainstream choices due to their high safety, low cost and long cycle life. However, the inherent defects of its cathode material, such as low electronic conductivity and one-dimensional lithium-ion diffusion channels, result in fast charging times generally exceeding 30 minutes in the 10%-80% SOC range, which is difficult to meet users' core demand for rapid energy replenishment. In addition, the battery has multiple kinetic bottlenecks, such as slow lithium-ion diffusion rate on the positive electrode side, easy lithium deposition on the negative electrode side during high-rate charging, and low electrolyte ion transport efficiency. Currently, the industry has conducted research on material modification, electrolyte design innovation, and system integration optimization to address these issues. For example, it has optimized positive and negative electrode materials through nano-sizing and carbon coating, improved electrolyte performance by using LiFSI lithium salt with low viscosity and high dielectric constant compound solvents and adding functional additives such as FEC and VC, and improved fast charging efficiency by building an 800V high-voltage platform and intelligent thermal management system. However, these technologies still have key pain points such as complex processes, high costs, material performance imbalances, and difficulty in achieving comprehensive electrolyte performance. It is urgent to break through the existing technical bottlenecks through innovative design of electrolyte systems to achieve a significant improvement in the fast charging performance of lithium iron phosphate power batteries.

[0003] Regarding the technical problem to be solved by this invention, there are currently some existing technologies. For example, CN201210007924.5: This invention relates to a method for preparing a lithium-ion secondary battery, which involves injecting an electrolyte A containing DMC and lithium salt into the battery, formation, injecting an electrolyte B containing DEC and lithium salt into the battery, and aging. This invention, by injecting an electrolyte A containing low-viscosity DMC into a soft-pack lithium-ion battery, facilitates the formation of a thin and dense SEI film during formation. Then, after formation, an electrolyte B containing DEC is injected, utilizing the ester exchange reaction between DMC and DEC to partially or completely convert the DMC with poor high-temperature resistance into EMC with good high-temperature resistance, greatly improving the performance of high-coated-weight soft-pack lithium-ion batteries. This invention differs fundamentally from this invention in its electrolyte formulation. The invention does not optimize the formulation for the fast-charging performance of LFP batteries, and its solvent viscosity and additive combination are difficult to meet the fast-charging requirements. CN201511007747.0: This invention aims to provide a lithium-ion battery with a PC-based electrolyte containing functional additives, and a secondary-filled electrolyte using PC as the main solvent. In this invention, the non-aqueous organic solvent includes PC as the main component, wherein PC constitutes 50%–100% of the total electrolyte mass, and the electrolyte salt is a lithium salt with a concentration of 2.5–4.0 mol / L. The secondary-filling method prevents the co-intercalation of PC solvent, thereby significantly improving the battery's initial efficiency, room-temperature cycle performance, and low-temperature discharge performance. This invention differs fundamentally from the present invention in its electrolyte formulation. The present invention optimizes the co-intercalation reaction of PC in the graphite anode through a design of high salt concentration and secondary-filling to regulate PC concentration; however, the excessively high lithium salt concentration in the electrolyte leads to a decrease in conductivity, affecting fast-charging performance. CN202010633904.3: This invention provides a battery and its preparation method. Electrolyte A can have a first additive added appropriately to form a more stable SEI film during formation. Electrolyte B can have a second additive added specifically based on the differences in battery material system or actual battery performance. This invention differs from the present invention in its electrolyte formulation. The present invention achieves both high and low temperature performance in LFP batteries by reasonably optimizing the proportion of secondary electrolyte additives, but it does not solve the problem of fast charging performance loss caused by high viscosity solvents. CN202111037145.5: This invention provides a method for electrolyte injection of lithium-ion batteries and its application. The solvents of the first and second electrolytes are consistent; the additives in the first electrolyte include low-resistance film-forming additives; the low-resistance film-forming additives are non-VC additives; the second electrolyte includes film-forming additives; the film-forming additives include VC.This invention, by adjusting the electrolyte during the electrolyte injection process, divides the SEI and CEI film formation in the battery into two stages, ensuring the stability of SEI and CEI and the long cycle life of the cell, effectively increasing the number of charge cycles and lifespan of the battery, and improving battery safety. This invention differs fundamentally from the present invention in its electrolyte formulation. The present invention achieves staged SEI and CEI film formation through reasonable optimization of secondary electrolyte injection additives, but introduces the problem of poor initial SEI structural stability due to the absence of VC in the first injection, which is detrimental to high-temperature cycling. CN202111349454.6: This invention provides a method for preparing a long-cycle-life lithium iron phosphate battery and its application. The electrolyte-injected battery is first injected with electrolyte A containing 1.5–2.5 wt% VC to obtain a semi-finished battery; a second injection is performed with electrolyte B containing 6.0–18.0 wt% VC to obtain a lithium iron phosphate battery. This invention optimizes the electrolyte solution and negative electrode material, and improves the cell design by using different electrolyte solutions for primary and secondary electrolyte injection. This reduces the battery's internal resistance and increases the content of residual electrolyte film-forming additive VC in the battery after formation and capacity testing, resulting in a longer cycle life and excellent electrochemical performance. This invention differs fundamentally from this one in its electrolyte formulation. While this invention achieves some reduction in battery internal resistance and improved cycle life by adjusting the proportion of VC in the secondary injection, the VC configuration in this solution can be further optimized. Reducing the proportion of VC in the primary injection and increasing the proportion in the secondary injection can further improve internal resistance and cycle life. Furthermore, this invention does not specifically optimize the solvent and lower impedance additive combination for fast charging performance. CN202111669579.7: This invention provides a lithium-ion battery electrolyte injection formation process and a lithium-ion battery. The primary injection uses electrolyte I with added low-impedance film-forming additives, which facilitates the formation of a low-impedance SEI film, thereby reducing the overall impedance of the cell; the secondary injection uses electrolyte II to ensure sufficient electrolyte volume in the battery. By adding different electrolytes twice in this process, the battery cell's performance in terms of both low impedance and long lifespan can be improved. This invention differs fundamentally from the present invention in its electrolyte formulation. This invention, by adjusting the proportion of additives in the second injection, achieves a certain effect in reducing battery internal resistance and improving cycle life. However, the VC configuration in this scheme can be further optimized; increasing the VC ratio in the second injection can further improve cycle life. Furthermore, this invention does not specifically design a combination of additives for lower impedance. CN202210223170.0: This invention relates to a lithium-ion battery electrolyte, an injection method, and a lithium-ion battery. The secondary electrolyte does not include lithium salt; additive B is at least one of phosphorus-based and sulfur-based additives containing unsaturated bonds. This invention differs fundamentally from the present invention in its electrolyte formulation. This invention, by introducing a unique additive in the first injection and without lithium salt in the second injection, achieves a certain effect in reducing viscosity and improving wetting. However, the overall lithium salt content in this scheme is relatively low, and the combination of additives in the first injection can be further optimized.CN202210249776.1: This invention discloses a method for secondary electrolyte injection in a high-power rechargeable battery; the electrolyte 1 used contains little or no vitamin C and contains FEC; the electrolyte 2 used contains vitamin C; the amount of vitamin C is 1.8-5 wt.% of the total weight of electrolyte 1 and electrolyte 2, and the amount of FEC is 0.8-2.2 wt.% of the total weight of electrolyte 1 and electrolyte 2. This invention achieves a balance between the battery's room temperature and low temperature power performance and its high temperature cycle performance by using secondary electrolyte injection and controlling the content of vitamin C and FEC in different injection processes. This invention differs fundamentally from this invention in its electrolyte formulation. This invention reduces the proportion of vitamin C in the first injection and uses FEC as the main component for initial film formation, which achieves a certain effect of reducing impedance. However, the initial SEI stability of this scheme is relatively low, and the combination of additives in the first injection can be further optimized.

[0004] The purpose of this invention is to resolve the contradiction between fast charging and cycle performance in existing lithium iron phosphate (LFP) system electrolyte technologies for fast-charging power lithium-ion batteries, as well as the difficulty in simultaneously achieving low interfacial impedance and high interfacial stability. Specifically, this invention aims to balance fast charging and cycle performance, low interfacial impedance, and high interfacial stability by employing an innovative secondary electrolyte injection method, rationally allocating vinylene carbonate (VC) content, and optimizing the injection volume ratio. This allows for control of SEI impedance during cell formation and effective SEI repair during long-term or high-temperature cycling, suppressing dehydrogenation side reactions of the solvent on the negative electrode surface. Furthermore, this invention aims to develop a solvent system with extremely low viscosity, controllable viscosity increase at low temperatures, and low overall polarity, which can accelerate the desolvation of lithium during fast charging, thereby improving fast charging and low-temperature performance. Simultaneously, it achieves dynamic adaptation to high-temperature cycling performance; even when a high content of a specific solvent is selected to pursue fast charging cycle performance, high-temperature cycling losses can be mitigated through lithium salts and additives. Furthermore, this invention improves lithium-ion conductivity, reduces interfacial impedance, and enhances interfacial stability through reasonable lithium salt blending and additive selection, delaying the increase of SEI interfacial impedance during cycling, while also considering cost while ensuring performance. Ultimately, it achieves technical effects such as 10%-80% actual charging time ≤19min, ≥1000 cycles (90%) at room temperature 2.2C fast charging, and ≥1300 cycles (80%) at high temperature, overcoming the contradiction between fast charging and cycling performance in existing technologies. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of the existing technology by providing a fast-charging lithium-ion battery electrolyte based on lithium iron phosphate.

[0006] The present invention is achieved through the following technical solution:

[0007] This invention provides a method for preparing a fast-charging power lithium-ion battery electrolyte based on lithium iron phosphate, which is achieved through a two-stage electrolyte injection method. The preparation method includes the following steps:

[0008] S1. The battery is initially filled with electrolyte A, which contains a small amount of vinylene carbonate (VC), as well as fluoroethylene carbonate (FEC) and vinyl sulfate (DTD). When the VC content is 0.5-1 wt.% during the initial filling, lithium difluorooxalate borate (LiODFB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiODFP), 1,3-propane sulpholactone (PS), methane disulfonate methylene (MMDS), and tris(trimethylsilyl)phosphate (TMSP) can be selectively added. During the initial filling, when the VC content is 0.5-1 wt.%, the initial SEI structural stability is relatively poor. The addition of FEC and DTD in this invention is mainly to adjust the SEI impedance rather than improve structural stability. Therefore, in order to improve the reduced battery storage performance caused by low VC content, this invention proposes to selectively add additives that improve SEI structural stability. Taking PS as an example, during the initial formation of SEI, the film-forming component of PS is mainly polysulfonate, which can be reduced and polymerized with VC to form a cross-linked network structure, thereby improving the initial structural stability of SEI.

[0009] S2. After the first electrolyte injection, the battery is placed and formed. This stage can be carried out at room temperature or at a combination of high temperature and room temperature. The total standing time is 2 to 72 hours, and the high temperature is 30 to 50 degrees Celsius.

[0010] S3. The battery undergoes a second electrolyte injection. The only additive in electrolyte B is VC, with an addition amount of 18–25 wt.%. After the second injection, the VC content in the electrolyte is 3–4 wt.% of the total weight of electrolytes A and B; the amount of FEC is 0.2–1 wt.% of the total weight of electrolytes A and B; and the amount of DTD is 0.2–1 wt.% of the total weight of electrolytes A and B. If the initial DTD content is too low, it will be insufficient to effectively form a low-impedance SEI; if the content is too high, it will lead to increased gas production during the formation stage, and the decomposition side reaction of DTD at high temperatures will cause increased acidity, leading to interface failure and performance degradation, while also increasing costs. If the initial FEC content is too low, it will be insufficient to effectively form a low-impedance SEI; if the content is too high, it cannot be completely consumed and will cause side reactions during subsequent high-temperature cycling, leading to gas production and degradation. Insufficient VC content cannot guarantee the VC consumption requirements and SEI membrane repair during long-term cycling, while excessive content hinders the mixing of the two electrolytes and increases costs. Existing technologies, to ensure cycling performance, primarily involve adding sufficient VC initially and supplementing with a small amount of VC a second time for long-term cycling, but this results in excessively high impedance and poor power. The main difference between this invention and existing technologies lies in the use of an appropriate amount of VC in the initial electrolyte injection, which also contains sufficient FEC and DTD. With the synergistic effect of the appropriate amount of VC and FEC / DTD, the film-forming impedance is low, and fast charging is good. A second sufficient amount of VC is then added for long-term cycling, resulting in better cycling performance.

[0011] After further optimization of the secondary electrolyte injection, the content of VC in the electrolyte is 3-4 wt.% of the total weight of electrolyte A and electrolyte B, the content of FEC is 0.2-1 wt.% of the total weight of electrolyte A and electrolyte B, and the content of DTD is 0.2-1 wt.% of the total weight of electrolyte A and electrolyte B.

[0012] This invention achieves a balance between low-temperature and fast-charging performance and high-temperature and cycle performance of the battery by using a two-stage electrolyte injection and synergistic control of the content of VC, FEC, and DTD during different electrolyte injection processes. Specifically, in the system of this invention, the addition of FEC and DTD as the main film-forming additives during the initial electrolyte injection reduces the consumption of VC in film formation, thereby improving power performance. This is because FEC and DTD preferentially undergo electrochemical decomposition on the negative electrode surface due to their higher reduction potential. The LiF crystals generated by FEC form the ion-conducting framework of the SEI film, while the ring-opening polymerization of DTD's thioester bonds forms a flexible support network. Meanwhile, VC undergoes reductive polymerization in the gaps of this composite framework, forming a mixed transition layer of Li2CO3 and organic polymers. This design utilizes the polymerization characteristics of VC to fill the pore defects after FEC / DTD film formation, while avoiding the thick film problem encountered when VC forms a film alone. This ternary film-forming system allows the SEI film formed during the initial electrolyte injection to possess the high ionic conductivity of LiF, the mechanical toughness of DTD, and the interfacial chemical stability of VC. This keeps the VC consumption during the initial injection below 1.5% (compared to 1.5% in traditional processes), while the VC from the secondary injection provides sufficient repair dose. This mechanism ensures low interfacial impedance during cell formation and achieves dynamic repair capability of the SEI film during cycling through a gradient VC consumption design, ultimately achieving synergistic optimization of fast-charging performance and high-temperature cycling stability.

[0013] S4. Allow the battery to stand to stabilize the SEI and free ions. After the second electrolyte injection, choose to first settling at high temperature and then at room temperature. At this point, the heat-sensitive additives in the electrolyte have been consumed, so high-temperature setting can effectively reduce the initial polarization of the battery and promote the completion of various reactions. Afterwards, setting the battery at room temperature reduces the battery temperature, effectively controlling cell polarization and improving product consistency and yield. The above setting can be either high temperature (30-50℃) + room temperature setting, or room temperature setting, with a total setting time of 2-72 hours.

[0014] S5. After electrolyte injection, perform capacity testing on the battery at room temperature; for example, the capacity testing temperature can be 25℃, and you can choose 1 / 3C capacity testing, 0.5C capacity testing, 1C capacity testing, etc.

[0015] In one embodiment of the present invention, the electrolyte A contains 0.5–1.5 wt.% VC, preferably 1–1.5 wt.% VC. The FEC content is 0.2–1.2 wt.% VC, preferably 0.5–1 wt.% FEC. The DTD content is 0.2–1.2 wt.% DTD, preferably 0.5–1 wt.% DTD.

[0016] In one embodiment of the present invention, the electrolyte A contains no additives other than VC, FEC, and DTD. That is, the electrolyte A contains only 0.5–1.5 wt.% vinylene carbonate, 0.2–1.2 wt.% fluoroethylene carbonate, and 0.2–1.2 wt.% vinyl sulfate. Preferably, it contains only 1–1.5 wt.% vinylene carbonate, 0.5–1 wt.% fluoroethylene carbonate, and 0.5–1 wt.% vinyl sulfate.

[0017] As one embodiment of the present invention, other additives are added to the electrolyte A. Specifically, when the VC content is 0.5-1 wt.% during the initial injection, other additives that improve the initial structural stability of the SEI can be added. These other additives include one or more of lithium difluorooxalatoborate (LiODFB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalatophosphate (LiODFP), 1,3-propanesulfonyl lactone (PS), methylene disulfonate (MMDS), and tris(trimethylsilyl)phosphate (TMSP). The content of these other additives in electrolyte A is 0.2-2 wt.%.

[0018] As one embodiment of the present invention, the solvent used in the electrolyte A is at least one of EC (ethylene carbonate), EMC (ethyl methyl carbonate), DMC (dimethyl carbonate), and EA (ethyl acetate), and must contain either DMC or EA, preferably EA.

[0019] In one embodiment of the present invention, the lithium salt in electrolyte A is a combination of LiPF6 (lithium hexafluorophosphate) and lithium bisfluorosulfonyl imide (LiFSI); the mass concentration of the lithium salt in electrolyte A is 10-15 wt.%. Preferably, the mass ratio of LiPF6 to LiFSI is 7:3.

[0020] In one embodiment of the present invention, the initial electrolyte injection volume is controlled at 80-95 wt.% of the total volume. Insufficient initial electrolyte injection volume will result in inadequate cell wetting, leading to lithium plating after formation. Excessive initial electrolyte injection volume will result in insufficient secondary electrolyte injection volume and excessively high required additive concentration, causing excessive concentration differences in additive distribution between the inner and outer layers of the electrode. More preferably, the initial electrolyte injection volume is controlled at 85-95 wt.% of the total volume; the secondary electrolyte injection volume is controlled at 5-20 wt.% of the total volume; and preferably, the amount of electrolyte B is 5-15 wt.% of the total volume.

[0021] In one embodiment of the present invention, the only additive in the electrolyte B is vitamin C, and the amount added is 18-25 wt.%, so that the total vitamin C content reaches 3-4 wt.%, FEC reaches 0.2-1 wt.%, and DTD reaches 0.2-1 wt.%.

[0022] In one embodiment of the present invention, the solvent used in the electrolyte B is 3 to 4 of EC, EMC, DMC, and EA, and must contain either DMC or EA, preferably EA. This improves the fast-charging performance of the battery cell and enhances its practicality. In this system, the introduction of DMC and EA at room temperature can effectively reduce the solvent viscosity, which would otherwise be detrimental to fast charging; when EA is used, the viscosity is even lower at low temperatures, resulting in better performance.

[0023] The solvent used in electrolyte B is the same as the solvent used in electrolyte A. Preferably, the solvents used in both the first and second electrolytes must contain EA.

[0024] In one embodiment of the present invention, the lithium salt in electrolyte B is a combination of LiPF6 and LiFSI; the molar concentration of the lithium salt in electrolyte B is 10-15 wt.%. Preferably, the mass ratio of LiPF6 to LiFSI is 7:3.

[0025] The additives include FEC and DTD in the first injection and VC after the second injection, with the content of each component as described in the gradient range above.

[0026] The above-mentioned additive combination of VC+FEC+DTD is selected for the first injection. Some technologies do not contain VC or contain very little VC, resulting in poor initial SEI stability, which affects high-temperature cycling performance; in some technologies, although the ratio of VC in the first and second injections is adjusted, the VC content in the first injection is still too high (1.5-2.5%), resulting in a larger initial SEI impedance, which is not conducive to fast charging performance.

[0027] The high VC content in the secondary injection solution primarily mitigates the side reactions of EA at the graphite anode. Since EA readily loses α-H on the anode surface during cycling, leading to decomposition and gas production, the high VC content in the secondary injection solution helps protect the interface, thereby improving high-temperature cycling. However, some solutions only contain 1-3% VC in the secondary injection, failing to achieve this effect.

[0028] Regarding the selection of other additives in the initial injection, when pursuing the ultimate fast charging performance, it is preferable to use an initial injection with a VC content of 0.5% to 1%. In this case, the combination with the "other additives" in this solution can, to a certain extent, compensate for the structural stability of the SEI and achieve the goal of taking into account high-temperature cycling.

[0029] The lithium salt used in electrolyte B is the same as the lithium salt used in electrolyte A.

[0030] In a preferred embodiment of the present invention, in step S2, the SOC of the formation stage is controlled to be 5-100%; and a low-resistivity SEI film is formed by a process of 30-50°C and pressurization to 500-2000 kgf.

[0031] In a further preferred embodiment, in step S2, the SOC during the formation stage is controlled to 45%; and through a high-temperature (45°C) and high-pressure (1500±50kgf) process, the synergistic film formation of FEC / DTD / VC is promoted to form a low-resistance SEI film, while taking into account production efficiency.

[0032] For example, in some embodiments, the process parameters for the high-temperature formation are: storage at 25°C after liquid injection, followed by high-temperature storage at 45°C, controlling the SOC during the formation stage to 45% SOC, the temperature of the formation fixture is 45°C, and the fixture pressure is 1500±50kgf.

[0033] As one embodiment of the present invention, a high-temperature aging step may be included before or after step S3; for example, the aging conditions are 45°C followed by 25°C.

[0034] This invention also provides a secondary power battery prepared according to the aforementioned method. The secondary power battery refers to a lithium-ion power battery. Specifically, the lithium-ion power battery refers to a lithium iron phosphate (LFP) lithium-ion power battery.

[0035] For example, the positive electrode of the secondary power battery is lithium iron phosphate, the negative electrode is graphite, and the separator is a PP separator.

[0036] The technical principles and key points involved in the above-mentioned lithium iron phosphate system fast-charging power lithium-ion battery electrolyte of this invention are mainly as follows:

[0037] 1. Gradient control mechanism of secondary injection

[0038] By gradient distribution of VC content between the first and second injections (0.5–1.5 wt.% VC in the first injection and 3–4 wt.% total VC content after the second injection), combined with the synergistic film-forming effect of FEC (0.2–1.2 wt.%) and DTD (0.2–1.2 wt.%), the dual function of "low-impedance film formation and dynamic repair" is achieved: In the first injection, FEC and DTD preferentially decompose to form the LiF ion-conducting framework and the DTD flexible network, and a small amount of VC fills the gaps to form a transition layer, reducing interfacial impedance; The VC supplemented by the second injection continuously repairs SEI film defects during cycling, balancing fast-charging performance and cycling stability.

[0039] 2. Synergistic effect of low viscosity and high dielectric constant of the solvent system

[0040] The solvent of electrolyte A must contain either DMC or EA, which, when combined with EC / EMC, forms a synergistic system with low viscosity (promoting Li+ migration) and high dielectric constant (optimizing solvation of the sheath), thus widening the liquid temperature range and improving ion conduction efficiency at both high and low temperatures.

[0041] 3. Kinetics and Interface Optimization of Lithium Salt Composite Systems

[0042] A lithium salt composed of LiPF6 and LiFSI (10-15 wt.%) was used to synergistically improve the ion conduction rate during fast charging by utilizing the high dissociation degree of LiPF6 and the low desolvation energy barrier of LiFSI. At the same time, the decomposition products of LiFSI were embedded in the SEI film to suppress the erosion of the interface by HF at high temperature.

[0043] 4. Composite structure design of SEI membrane

[0044] A composite SEI film consisting of a LiF crystal framework, a DTD polymer network, and a VC organic transition layer was constructed using a FEC / DTD / VC ternary film-forming system, exhibiting high ion conductivity, mechanical toughness, and chemical stability. It was also specified that when the VC content in electrolyte A is 0.5–1 wt.%, other additives can be selected to compensate for insufficient SEI stability.

[0045] Beneficial effects:

[0046] This invention achieves a balance between low-temperature and fast-charging performance and high-temperature and cycle performance of the battery by using a two-stage electrolyte injection process and synergistic control of the VC, FEC, and DTD content during different injection stages. Compared with existing technologies, this invention has the following advantages:

[0047] (1) Construction of low-impedance SEI film and improvement of fast charging performance

[0048] In the initial electrolyte injection of this invention, FEC and DTD are used as the main film-forming additives. Utilizing their higher reduction potentials, they preferentially decompose on the negative electrode surface. The LiF crystals generated by FEC form the ion-conducting framework of the SEI film, while the thioester bonds of DTD undergo ring-opening polymerization to form a flexible support network. A small amount of VC undergoes reduction polymerization in the gaps between the composite frameworks, forming a mixed transition layer of Li2CO3 and organic polymers. This ternary film-forming system avoids the problem of thick films formed by VC alone, enabling the SEI film to possess the high ion conductivity of LiF, the mechanical toughness of DTD, and the interfacial chemical stability of VC. This reduces the interfacial impedance during the formation stage, thereby significantly improving the battery's room-temperature fast-charging / low-temperature performance.

[0049] (2) Optimization of SEI membrane dynamic repair capability and high-temperature cycling stability

[0050] Sufficient VC is replenished during secondary electrolyte injection, and dynamic repair of the SEI film is achieved through a gradient consumption design: the VC consumption during the initial electrolyte injection is controlled within 1.5% (compared to 1.5% in conventional processes), and the VC from the secondary injection continuously fills the pore defects of the SEI film during high-temperature cycling, inhibiting interface failure caused by HF erosion. This mechanism solves the problems of increased impedance due to excessive VC during the initial injection or cycle degradation caused by insufficient secondary electrolyte injection in existing technologies. It enables the battery to maintain the chemical stability of the interface film under high-temperature conditions, avoiding capacity decay caused by SEI film rupture.

[0051] (3) Collaborative optimization of multi-dimensional performance

[0052] By gradient regulation of VC, FEC, and DTD contents during two injection cycles, a synergistic mechanism of "low-resistance film formation during the first injection and dynamic repair during the second injection" is formed: the ternary system of FEC / DTD / VC in the first injection ensures low polarization characteristics during the formation stage, meeting the requirements for fast charging; the VC reserve (18-25 wt.%) in the second injection provides interface repair capability for long-term cycling and can effectively suppress the dehydrogenation side reaction of EA on the graphite anode surface. When the VC content in the second injection is below 18 wt.%, it has no significant effect, while avoiding high-temperature side reactions caused by excessive FEC / DTD. This design overcomes the contradiction between fast charging performance and high-temperature cycling stability in existing technologies, enabling the battery to have both excellent fast charging and cycle life over a wide temperature range (25℃-45℃).

[0053] (4) Synergistic optimization of solvent system on fast-charging ion conduction characteristics

[0054] This invention specifies that the solvent system of electrolyte A must contain either DMC (dimethyl carbonate) or EA (ethyl acetate), preferably EA, because its low viscosity properties create a synergistic effect with high dielectric constant solvents (such as EC): the linear molecular structure of DMC / EA can reduce the overall viscosity of the electrolyte and significantly improve the Li... + The migration rate in the solvent, and its complex system with EC / EMC can optimize the solvation sheath structure, making Li + The desolvation energy barrier is lowered. During fast charging, this solvent system improves performance through the following mechanisms:

[0055] Optimization of ion conduction: The low viscosity at room temperature of DMC / EA shortens the Li + The transport path in the electrolyte, combined with the high dielectric constant environment provided by EC, allows the electrolyte to maintain high ionic conductivity during high-rate charge and discharge, reducing concentration polarization; furthermore, the low-temperature and low-viscosity characteristics of EA can further improve the lithium-ion transport effect.

[0056] Improved temperature adaptability: The addition of DMC / EA widens the liquid temperature range of the electrolyte (-30℃ to 80℃), maintaining stable ion conduction capacity under both high and low temperature conditions, and avoiding the degradation of fast charging performance caused by a sudden increase in solvent viscosity or decomposition.

[0057] (5) Synergistic optimization of fast charging dynamics and high-temperature interface stability of lithium salt composite system

[0058] The electrolyte of this invention uses a LiPF6 and LiFSI compound lithium salt system (10-15 wt.%). Through the synergistic effect of the ion conduction characteristics and interface regulation function of the two, it achieves a dual improvement in fast charging performance and high-temperature cycling stability. Its mechanism of action is as follows:

[0059] ① Optimization of ion conduction kinetics during fast charging

[0060] The high dissociation degree of LiPF6 complements the low solvation barrier of LiFSI: LiPF6 provides a high concentration of free Li + Shortening the ion transport path during fast charging; the bis(fluorosulfonyl)imide anion (FSI) of LiFSI - ) and Li + The resulting solvated sheath structure is more easily dissociated, making Li + The desolvation energy barrier is lowered. This compound system can maintain high ionic conductivity during high-rate charge and discharge. Combined with the low viscosity of the solvent system, it reduces concentration polarization and avoids the risk of lithium plating on the negative electrode caused by ion transport lag.

[0061] ② Regulation of interfacial chemical stability during high-temperature cycling

[0062] The LiF and Li₂SO₃ components produced by the high-temperature decomposition of LiFSI can be embedded into the SEI film lattice, forming a gradient structure with the LiF / DTD / VC composite film formed during the initial liquid injection: LiF crystals enhance the ion conductivity of the SEI film, while Li₂SO₃ inhibits the corrosion of the cathode material by HF. Simultaneously, the PF₅ produced by the decomposition of LiPF₆ interacts with the FSI of LiFSI. - A coordination reaction occurs, forming PF5·FSI. - The complex reduces the decomposition rate of lithium salts at high temperatures, thereby suppressing impedance growth caused by interfacial side reactions at the source.

[0063] ③ Synergistic regulation of interfacial equilibrium by lithium salt concentration gradient

[0064] A lithium salt concentration of 10–15 wt.% balances ion transport and solvation: higher concentrations of Li + Compressible solvation sheath thickness accelerates Li +Migration at the electrolyte-SEI membrane interface; the mass ratio of LiPF6 to LiFSI (e.g., 7:3) optimizes the coordination ratio of anions in the solvated sheath, achieving a dynamic balance between the deposition rate of the SEI membrane precursor (e.g., LiF, Li2CO3) and the electrolyte permeation rate, thus avoiding problems such as loose or excessively thick SEI membranes caused by lithium salt concentration imbalance. This design maintains stable interfacial ion transport performance within a temperature range of -20℃ to 60℃, achieving synergistic optimization of wide-temperature fast charging and high-temperature cycling.

[0065] (6) Initial SEI structural stability regulation

[0066] This invention indicates that if the amount of VC added during the initial electrolyte injection is 0.5–1 wt.%, additives to improve the initial structural stability of the SEI can be selectively added. These other additives include one or more of lithium difluorooxalatoborate (LiODFB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalatophosphate (LiODFP), 1,3-propanesulfonyl lactone (PS), methylene disulfonate (MMDS), and tris(trimethylsilyl)phosphate (TMSP). The content of other additives in electrolyte A is 0.2–2 wt.%.

[0067] In existing technologies, the pursuit of fast-charging performance often overlooks the poor initial structural stability of the SEI (Sediment Ion Exchange), especially in some technical solutions that lack VC (Volume Capacitor). While such SEIs exhibit good ion conduction, they are susceptible to rupture due to polarization shocks during battery storage or early cycling, leading to the depletion of active lithium ions and ultimately resulting in poor battery capacity recovery or rapid initial capacity decay.

[0068] In this invention, on the one hand, a certain amount of VC is ensured during the initial film formation; on the other hand, to compensate for the poor SEI structural stability caused by insufficient VC (the film-forming product is a polymer with high SEI stability), additives that can synergistically react with VC to form a film can be selectively introduced. Their reaction products can crosslink or embed into the reduced polymer of VC, thereby improving the initial SEI structural stability. Furthermore, these additives primarily promote synergistic film formation, thus requiring a lower addition amount, while also addressing the need for low SEI resistance.

[0069] In summary, this invention controls the VC content through a secondary electrolyte injection gradient to avoid the impedance increase caused by excessive VC in the initial injection. Simultaneously, it reduces polarization through preferential film formation using FEC / DTD. All three are essential. Furthermore, it proposes that when VC is insufficient in the initial film formation stage, other additives should be added to compensate for the structural stability loss of the SEI. To improve the fast-charging performance of the cell and emphasize practicality, this invention selects specific solvents: EMC, EC, DMC, and EA, with DMC and EA being mandatory, and EA being preferred. The VC content in the secondary electrolyte injection primarily mitigates the side reactions of EA on the graphite anode, ultimately achieving the dual goals of "fast charging with low impedance" and "high cycle stability." Detailed Implementation

[0070] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0071] The present invention provides a method for secondary electrolyte injection into a secondary battery, which includes the following steps:

[0072] The secondary electrolyte injection method for secondary batteries proposed in this invention involves two electrolyte options: electrolyte A and electrolyte B.

[0073] The present invention operates as follows: During the initial electrolyte filling, electrolyte A is used. Unlike other inventions that use a higher content of VC, the present invention reduces the amount of VC used and uses other additives to form a thin and dense SEI film during the battery formation process. Electrolyte A contains a small amount of VC and also contains FEC and DTD. The VC content is controlled at 0.5–1.5 wt.%, preferably 1–1.5 wt.%, the FEC content is controlled at 0.2–1.2 wt.%, preferably 0.5–1 wt.%, and the DTD content is controlled at 0.2–1.2 wt.%, preferably 0.5–1 wt.%. After electrolyte filling, the battery is subjected to room temperature and high temperature settling and formation. The main purpose of this formation stage is to completely consume the film-forming additives, allowing a stable, dense, and thin SEI layer to form on the negative electrode.

[0074] The method for secondary electrolyte injection of a power battery provided by the present invention includes the following steps:

[0075] S1: Electrolyte A is used in the initial electrolyte filling of the battery.

[0076] The initial injection volume is controlled at 80-95% of the total volume, preferably 85-95 wt.% of the total volume.

[0077] The solvent is 3 to 4 of the following: EC (ethylene carbonate), EMC (ethyl methyl carbonate), DMC (dimethyl carbonate), and EA (ethyl acetate), and must contain either DMC or EA, with EA being preferred.

[0078] The lithium salt is a combination of LiPF6 (lithium hexafluorophosphate) and lithium bis(fluorosulfonyl)imide (LiFSI).

[0079] When the amount of VC added in electrolyte A is 0.5 to 1 wt.%, other additives can be selected from one or more of lithium difluorooxalate borate (LiODFB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiODFP), 1,3-propane sulpholactone (PS), methylene methane disulfonate (MMDS), and tris(trimethylsilyl) phosphate (TMSP).

[0080] By using this method, a thin and dense SEI film can be formed in the battery, reducing battery impedance and achieving the goals of improving fast charging and ensuring high-temperature cycling.

[0081] S2: After electrolyte injection, the battery undergoes room temperature, high temperature resting, and high temperature pressurization formation to control the SOC (State of Charge) to 45% during the formation stage. The main purpose of this formation stage is to completely consume the film-forming additives, allowing the negative electrode to form a stable, dense, and thin SEI layer. Room temperature resting is preferred after electrolyte injection to ensure effective electrolyte wetting, followed by a short period of high temperature resting to ensure sufficient electrolyte wetting. If the high temperature resting temperature is too high or the time is too long, the DTD in the electrolyte is prone to hydrolysis under high temperature conditions, forming acidic substances. These acidic substances are detrimental to the later battery performance and reduce the effective DTD content. Furthermore, the formation process proposed in this invention effectively balances film formation and production efficiency. It ensures that the low current and voltage range can cover the film-forming reaction potential of the additives in this invention, that the stepwise increase in charging current improves production efficiency, and that high temperature pressurization promotes accelerated additive reduction and gas removal, resulting in a good overall interface.

[0082] S3: Perform a second electrolyte filling on the battery, using electrolyte B, with additives including vinylene carbonate (VC), added at a rate of 18–25 wt.%. The concentration of VC used should be appropriate so that the total concentration of the two electrolytes after mixing is 3–4 wt.

[0083] S4: The battery undergoes high-temperature and then room-temperature settling to stabilize the SEI and free ions. After the second electrolyte filling, a high-temperature initial settling followed by room-temperature settling is performed. At this point, heat-sensitive additives in the electrolyte have been consumed, thus high-temperature settling effectively reduces initial battery polarization and promotes the completion of various reactions. Subsequent room-temperature settling lowers the battery temperature, effectively controlling cell polarization and improving product consistency and yield.

[0084] Preferably, in this embodiment, the VC content in the secondary injection solution is 18-25 wt.%, for example, 18-23 wt.%, and the total VC concentration after mixing with the electrolyte is 3-4 wt.%.

[0085] The secondary injection volume is controlled at 5-20 wt.% of the total volume; preferably, the amount of electrolyte B is 5-15 wt.% of the total volume.

[0086] The solvent and lithium salt used in electrolyte B are the same as those used in electrolyte A.

[0087] S5: After electrolyte injection, perform capacity testing on the battery at room temperature; the capacity testing temperature is 25℃.

[0088] See the following examples for details:

[0089] The following examples and comparative examples use the same positive electrode, negative electrode, and separator. The positive electrode is lithium iron phosphate; the negative electrode is graphite; and the separator is a PP separator.

[0090] Example 1

[0091] This embodiment provides a method for secondary electrolyte injection into a power battery, wherein the positive electrode of the power battery is lithium iron phosphate, the negative electrode is graphite, and the separator is a PP separator.

[0092] The secondary injection method includes the following steps:

[0093] S1: In the initial electrolyte filling of the battery, electrolyte A is used, and the initial filling volume is controlled at 85 wt.% of the total volume; the specific composition of electrolyte A is: EMC:EC:EA = 1:1:1 (mass ratio), LiPF6 is 10 wt.%, LiFSI is 3 wt.%, VC is 1 wt.%, PS is 1 wt.%, FEC is 1 wt.%, and DTD is 1 wt.%.

[0094] S2: After electrolyte injection, the battery is placed at room temperature and high temperature for formation. After electrolyte injection, it is placed at 25°C and then stored at 45°C to control the SOC of the formation stage to 45%. The temperature of the formation fixture is 45°C and the fixture pressure is 1500±50kgf.

[0095] S3: Perform a second electrolyte injection on the battery, using electrolyte B, with additives including vinylene carbonate (VC), and the concentration of VC used is 20%; the type and content of solvent and lithium salt used in electrolyte B are the same as those in electrolyte A.

[0096] S4: The battery is placed at high temperature and then at room temperature. The placement conditions are 45℃ and then 25℃.

[0097] S5: After electrolyte injection, perform capacity testing of the battery at room temperature;

[0098] Example 2

[0099] This embodiment provides a method for secondary electrolyte injection into a power battery, which is basically the same as in Embodiment 1, except that the VC of electrolyte A is 1.5 wt.%.

[0100] Example 3

[0101] This embodiment provides a method for secondary electrolyte injection of a power battery, which is basically the same as that in Embodiment 1, except that PS in electrolyte A is replaced with LiODFB.

[0102] Example 4

[0103] This embodiment provides a method for secondary electrolyte injection of a power battery, which is basically the same as that in Embodiment 1, except that PS in electrolyte A is replaced with LiPO2F2.

[0104] Example 5

[0105] This embodiment provides a method for secondary electrolyte injection of a power battery, which is basically the same as that in Embodiment 1, except that the PS in electrolyte A is replaced with LiODFP.

[0106] Example 6

[0107] This embodiment provides a method for secondary electrolyte injection of a power battery, which is basically the same as that in Embodiment 1, except that the PS in electrolyte A is replaced with MMDS.

[0108] Example 7

[0109] This embodiment provides a method for secondary electrolyte injection of a power battery, which is basically the same as that in Embodiment 1, except that the PS in electrolyte A is replaced with TMSP.

[0110] Comparative Example 1 (Standard 1-injection process)

[0111] The difference between this comparative example and Example 1 is that a conventional electrolyte injection method was used. The specific composition of the electrolyte is: EMC:EC:EA = 1:1:1 (mass ratio), LiPF6 10 wt.%, LiFSI 3 wt.%, VC 3.85 wt.%, PS 1 wt.%, FEC 1 wt.%, and DTD 1 wt.%.

[0112] Comparative Example 2 (low betting volume)

[0113] The difference between this comparative example and Example 1 is that the ratio of one bet is reduced to 70%, and the ratio of two bets is increased to 30%.

[0114] Comparative Example 3 (One bet volume is too high)

[0115] The difference between this comparative example and Example 1 is that it provides a first bet ratio of up to 98%, and the corresponding second bet ratio is reduced to 2%.

[0116] Comparative Example 4 (High Solvent Viscosity)

[0117] The difference between this comparative example and Example 1 is that the solvents for electrolytes A and B are EMC:EC = 70:30.

[0118] Comparative Example 5 (low lithium salt content)

[0119] The difference between this comparative example and Example 1 is that the lithium salts in electrolytes A and B are: 5 wt.% LiPF6 and 1 wt.% LiFSI.

[0120] Comparative Example 6 (without FSI)

[0121] The difference between this comparative example and Example 1 is that the lithium salt in electrolytes A and B is 10 wt.% LiPF6.

[0122] Comparative Example 7 (One bet with low VC)

[0123] The difference between this comparative example and Example 1 is that the VC content in electrolyte A is 0.3 wt.%.

[0124] Comparative Example 8 (One bet with no VC and high FEC)

[0125] The difference between this comparative example and Example 1 is that electrolyte A does not contain VC and PS, FEC is 1.8 wt.%, and LiPO2F2 is 0.8 wt.%, while electrolyte B uses VC at a concentration that is adapted to the total concentration of the two electrolytes after mixing, which is 2 wt.%.

[0126] Comparative Example 9 (FEC and DTD are low)

[0127] The difference between this comparative example and Example 1 is that the FEC content in electrolyte A is 0.1 wt.% and the DTD content is 0.1 wt.%.

[0128] Comparative Example 10 (excluding FEC and DTD)

[0129] The difference between this comparative example and Example 1 is that electrolyte A does not contain PS, FEC, and DTD.

[0130] Comparative Example 11 (excluding DTD)

[0131] The difference between this comparative example and Example 1 is that electrolyte A does not contain DTD.

[0132] Comparative Example 12 (excluding FEC)

[0133] The difference between this comparative example and Example 1 is that electrolyte A does not contain FEC.

[0134] Comparative Example 13 (no other additives added when VC ≤ 1.5%)

[0135] The difference between this comparative example and Example 1 is that electrolyte A does not contain PS.

[0136] The assembled lithium-ion batteries in the comparative examples and embodiments were subjected to a 2.2C step charge and 1C discharge cycle at 25°C to test capacity retention, with a voltage range of 2.5–3.65V. The actual charging time from 10% to 80% was 19 minutes.

[0137] The results are shown in Table 1:

[0138] Table 1. Room temperature 2.2C fast charging cycle performance test

[0139]

[0140]

[0141] The assembled lithium-ion batteries in the comparative examples and embodiments were subjected to 1C step charge and 1C discharge cycles at 45°C to test capacity retention within a voltage range of 2.5–3.65V. The results are shown in Table 2.

[0142] Table 2 High-Temperature Cyclic Performance Test

[0143]

[0144]

[0145] The assembled lithium-ion batteries in the above comparative examples and embodiments were tested for DCR after 2C charging for 2 seconds at 50% SOC in an environment of 25°C.

[0146] The results are shown in Table 3:

[0147] Table 3 DCR Test Results

[0148]

[0149]

[0150] By comparing "Comparative Example 1" and "Example 1", it can be seen that after adopting the secondary electrolyte injection process of the present invention, the DCR is significantly reduced, which can significantly improve the room temperature fast charge cycle performance of the battery. The high VC concentration in Comparative Example 1 participates in the first film formation, which can significantly improve SEI stability and achieve excellent high temperature cycle performance. However, due to the high SEI impedance, the room temperature fast charge cycle performance decays relatively quickly.

[0151] A comparison of "Comparative Example 2" and "Example 1" shows that after adopting the secondary electrolyte injection ratio of the present invention, the DCR is significantly reduced, which can significantly improve the battery's room temperature fast charging cycle performance and high temperature cycle performance. In Comparative Example 2, the electrolyte A injection volume was low, and the insufficient additives for the initial film-forming effect resulted in poor film-forming effect, which is not conducive to the performance of the cycle.

[0152] By comparing "Comparative Example 3" and "Example 1", it can be seen that after adopting the secondary electrolyte injection ratio of the present invention, the DCR is significantly reduced, which can significantly improve the room temperature fast charge cycle performance of the battery. In Comparative Example 3, the electrolyte A injection volume is relatively high, and the VC in the first film formation is excessive, which can significantly improve SEI stability and achieve excellent high temperature cycle performance. However, due to the high SEI impedance, the room temperature fast charge cycle performance decays relatively quickly.

[0153] A comparison of "Comparative Example 4" and "Example 1" shows that using the solvent of the present invention significantly reduces the DCR, thereby significantly improving the battery's room-temperature fast-charge cycle performance. The solvent in Comparative Example 4 has a high viscosity, which is not conducive to fast-charge cycle performance; however, it has good high-temperature adaptability, thus giving it an advantage in high-temperature cycle performance.

[0154] A comparison of "Comparative Example 5" and "Example 1" shows that by using the lithium salt content of the present invention, the DCR is significantly reduced, which can significantly improve the battery's room temperature fast charging cycle performance and high temperature cycle performance. The lithium salt content in Comparative Example 5 is relatively low, which is detrimental to the performance of the cycle cycle.

[0155] A comparison of "Comparative Example 6" and "Example 1" shows that using the lithium salt of this invention significantly reduces the DCR, resulting in a marked improvement in the battery's room-temperature fast-charge cycle performance and high-temperature cycle performance. Comparative Example 6 does not contain LiFSI, which is detrimental to its cycle performance.

[0156] By comparing "Comparative Example 7" and "Example 1", it can be seen that using the VC content of electrolyte A of the present invention can significantly improve the battery's room temperature fast charging cycle performance and high temperature cycle performance. In Comparative Example 7, the VC content of electrolyte A in one injection is relatively low. Although the DCR is low, the SEI structure stability is poor, which is not conducive to the performance of the cycle.

[0157] A comparison of "Comparative Example 8" and "Example 1" shows that using the additives in electrolyte A of the present invention can significantly improve the battery's room temperature fast-charge cycle performance and high-temperature cycle performance. In Comparative Example 8, electrolyte A, lacking VC, has a lower DCR, but its initial SEI stability is poor, which is detrimental to its cycle performance.

[0158] By comparing "Comparative Example 9" and "Example 1", it can be seen that after adopting the FEC and DTD ratio of electrolyte A of the present invention, the DCR is significantly reduced, which can significantly improve the battery's room temperature fast charging cycle performance and high temperature cycle performance. In Comparative Example 9, the FEC and DTD content of electrolyte A in one injection is relatively low, resulting in poor initial SEI stability and high impedance, which is not conducive to the performance of the cycle.

[0159] By comparing "Comparative Example 10" and "Example 1", it can be seen that after adopting the FEC and DTD ratio of electrolyte A of the present invention, the DCR is significantly reduced, which can significantly improve the battery's room temperature fast charging cycle performance and high temperature cycle performance. In Comparative Example 10, one batch of electrolyte A does not contain FEC and DTD, resulting in poor initial SEI stability and high impedance, which is not conducive to the performance of the cycle.

[0160] By comparing "Comparative Example 11" and "Example 1", it can be seen that after adopting the DTD ratio of electrolyte A of the present invention, the DCR is significantly reduced, which can significantly improve the battery's room temperature fast charging cycle performance and high temperature cycle performance. In Comparative Example 11, one batch of electrolyte A does not contain DTD, resulting in poor initial SEI stability and high impedance, which is not conducive to the performance of the cycle.

[0161] By comparing "Comparative Example 12" and "Example 1", it can be seen that after adopting the FEC ratio of electrolyte A of the present invention, the DCR is significantly reduced, which can significantly improve the battery's room temperature fast charge cycle performance and high temperature cycle performance. In Comparative Example 12, one batch of electrolyte A does not contain FEC, resulting in poor initial SEI stability and high impedance, which is not conducive to the performance of the cycle.

[0162] By comparing "Comparative Example 13" and "Example 1", it can be seen that using "other additives PS" in electrolyte A of the present invention can significantly improve the battery's room temperature fast charging cycle performance and high temperature cycle performance. In Comparative Example 13, one batch of electrolyte A does not contain PS, and although the DCR is lower, the initial film-forming SEI stability is poor, which is not conducive to the performance of the cycle.

[0163] The forced charging time is 19 minutes, but the fast charging performance is poor. It cannot charge to 80% SOC before jumping to the next step to start full charging.

[0164] The above embodiments of the present invention fully demonstrate that the proposed solution has a charging time of ≤19min from 10% to 80%, a capacity retention rate of >90% after ≥1000 cycles at room temperature (2.2C), and a capacity retention rate of >80% after ≥1300 cycles at high temperature (45℃). This solution overcomes the contradiction between fast charging and cycle performance in the prior art, thus achieving excellent technical results.

[0165] It is evident that the core beneficial effect of the present invention lies in:

[0166] (1) Synergistic improvement of low-impedance SEI film construction and fast charging performance

[0167] By using a ternary film-forming system of FEC, DTD and a small amount of VC in the initial liquid injection, a composite structure of "LiF ion conduction framework-DTD flexible network-VC transition layer" is formed, avoiding the problem of thick film formation in traditional VC film formation alone, thus significantly improving the battery's fast charging performance at room temperature.

[0168] (2) Breakthrough in SEI membrane dynamic repair mechanism and high-temperature cycling stability

[0169] Sufficient VC is added during the second injection, and interface repair during cycling is achieved through "gradient consumption design": the VC consumption during the first injection is controlled within 1.5% to avoid a sudden increase in impedance; the VC from the second injection continuously fills the defects in the SEI film during high-temperature (45℃) cycling, inhibiting HF erosion, thus resolving the contradiction that "high VC improves high-temperature performance but worsens fast-charging degradation".

[0170] (3) Multi-dimensional synergistic optimization of wide temperature range performance

[0171] Through additive gradient regulation via two injection cycles, a synergistic mechanism of "low-resistance film formation - dynamic repair" is formed: First injection: The FEC / DTD / VC system reduces polarization to meet fast charging requirements; Second injection: VC reserves enhance high-temperature cycle life. Within the temperature range of 25℃~45℃, the battery simultaneously achieves: a capacity retention rate of >90% after 1000 cycles of room-temperature fast charging (2.2C / 1C); and a capacity retention rate of >80% after 1300 cycles of high-temperature cycling (1C / 1C), overcoming the bottleneck of "mutual exclusion between fast charging and high-temperature performance" in existing technologies.

[0172] (4) Temperature adaptability optimization of solvent system to ion conduction properties

[0173] Adding DMC / EA, a low-viscosity solvent, to electrolyte A creates a synergistic effect with EC (a high-viscosity solvent): Low viscosity characteristic: reduces electrolyte viscosity, Li + Migration speed improved.

[0174] (5) Dual regulation of fast charging kinetics and interface stability by lithium salt composite system

[0175] Lithium salts are formulated using LiPF6 / LiFSI (10–15 wt.%).

[0176] Fast charging kinetics optimization: LiPF6 provides high concentration of Li + LiFSI lowers the desolvation energy barrier, resulting in a lower polarization voltage during 2.2C charging.

[0177] High-temperature interface stability: LiFSI decomposes to generate LiF / Li2SO3 which is embedded in the SEI film, inhibiting HF erosion.

[0178] (6) Initial SEI structural stability regulation

[0179] In this invention, on the one hand, a certain amount of VC is ensured during the initial film formation; on the other hand, to compensate for the poor SEI structural stability caused by insufficient VC (the film-forming product is a polymer with high SEI stability), additives that can synergistically react with VC to form a film can be selectively introduced. Their reaction products can crosslink or embed into the reduced polymer of VC, thereby improving the initial SEI structural stability. Furthermore, these additives primarily promote synergistic film formation, thus requiring a lower addition amount, while also addressing the need for low SEI resistance.

[0180] This invention overcomes the problem of "contradiction between fast charging performance and high-temperature cycling" in the prior art through a multi-dimensional design of "secondary liquid injection gradient control + additive synergistic film formation + solvent / lithium salt system optimization", enabling the battery to have both long life and fast charging capability.

[0181] Obviously, the above embodiments are merely examples for clear illustration and are not intended to limit the embodiments. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all embodiments here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A preparation method of a lithium iron phosphate system fast-charging power lithium ion battery electrolyte, which is realized by a secondary injection method, characterized in that, The preparation method comprises the following steps: S1: first liquid injection is performed on the battery, the electrolyte A used contains 0.5-1.5 wt.% of vinylene carbonate (VC), and contains fluoroethylene carbonate (FEC) and vinyl sulfate (DTD), solvent and lithium salt; according to the content of vinylene carbonate in the electrolyte A, the electrolyte A can also contain other additives; S2: after the first liquid injection, the battery is placed and formed; S3: secondary liquid injection is performed on the battery, the additive in the electrolyte B used is 18-25 wt.% of vinylene carbonate (VC), solvent and lithium salt; S4: the battery is placed to stabilize the SEI and free ions; S5: after the liquid injection, the battery is divided at room temperature; Preferably, the first liquid injection amount is controlled to be 85-95 wt.% of the total amount.

2. The preparation method of the lithium iron phosphate system fast-charging power lithium ion battery electrolyte according to claim 1, characterized in that, In the secondary liquid injection method, when the first liquid injection is performed, the content of vinylene carbonate (VC) in the electrolyte A is 0.5-1.5 wt.%, the content of fluoroethylene carbonate (FEC) is 0.2-1.2 wt.%, and the content of vinyl sulfate (DTD) is 0.2-1.2 wt.%; preferably, the content of vinylene carbonate (VC) is 1-1.5 wt.%, the content of fluoroethylene carbonate (FEC) is 0.5-1 wt.%, and the content of vinyl sulfate (DTD) is 0.5-1 wt.%.

3. The preparation method of the lithium iron phosphate system fast-charging power lithium ion battery electrolyte according to claim 1, characterized in that, In the secondary liquid injection method, the electrolyte A contains 0.5-1.5 wt.% of vinylene carbonate (VC) and 0.2-1.2 wt.% of fluoroethylene carbonate (FEC) and 0.2-1.2 wt.% of vinyl sulfate (DTD); preferably, the electrolyte A contains 1-1.5 wt.% of vinylene carbonate (VC) and 0.5-1 wt.% of fluoroethylene carbonate (FEC) and 0.5-1 wt.% of vinyl sulfate (DTD).

4. The preparation method of the lithium iron phosphate system fast-charging power lithium ion battery electrolyte according to claim 1 or 2, characterized in that, In the secondary liquid injection method, when the first liquid injection is performed with 0.5-1 wt.% of vinylene carbonate (VC), other additives can be contained, the other additives are at least one of lithium difluoro(oxalato)borate (LiODFB), lithium difluorophosphate (LiPO2F2), lithium difluorophosphate (LiODFP), 1,3-propane sultone (PS), methylene methanedisulfonate (MMDS), and tris(trimethylsilyl) phosphate (TMSP); the content of the other additives in the electrolyte A is 0.2-2 wt.%.

5. The preparation method of the lithium iron phosphate system fast-charging power lithium ion battery electrolyte according to claim 1, characterized in that, In the secondary liquid injection method, the solvent used in the electrolyte A and B is at least one of vinyl carbonate, methyl ethyl carbonate, dimethyl carbonate, and ethyl acetate.

6. The preparation method of the lithium iron phosphate system fast-charging power lithium ion battery electrolyte according to claim 1, characterized in that, Further, in the secondary liquid injection method, the solvent used in the electrolyte A and B is at least one of dimethyl carbonate and ethyl acetate; more preferably, the solvent is ethyl acetate.

7. The preparation method of the lithium iron phosphate system fast-charging power lithium ion battery electrolyte according to claim 1, characterized in that, The lithium salt in the electrolyte A and B is a combination of lithium hexafluorophosphate and lithium bisfluorosulfonylimide; the mass concentration of the lithium salt in the electrolyte A and B is 10-15 wt.%.

8. The preparation method of the lithium iron phosphate system fast-charging power lithium ion battery electrolyte according to claim 1, characterized in that, After the secondary injection, the content of vinylene carbonate (VC) in the electrolyte is 3-4 wt.% of the total weight of electrolyte A and electrolyte B; the amount of fluoroethylene carbonate (FEC) is 0.2-1 wt.% of the total weight of electrolyte A and electrolyte B; the amount of vinyl sulfate (DTD) is 0.2-1 wt.% of the total weight of electrolyte A and electrolyte B.

9. The preparation method of the lithium iron phosphate system fast-charging power lithium ion battery electrolyte according to claim 1, characterized in that, In the method of the secondary injection, in step S2, the SOC of the formation stage is controlled to be 5-100% SOC; and a low impedance SEI film is formed by a process of 30-50°C and pressurization to 500-2000 kgf; a step of high temperature aging can be further included before or after step S3.

10. A secondary power cell characterized by The secondary power battery is a lithium ion power battery, and the secondary power battery comprises the fast-charging type power lithium ion battery electrolyte prepared by the preparation method in any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of lithium ion secondary battery

    CN102738513A

  • Electrolyte taking propylene carbonate as main solvent and secondarily liquid injected lithium ion battery

    CN105449281A

  • Battery and preparation method thereof

    CN111628225A

  • Preparation method and application of lithium iron phosphate battery with long cycle life

    CN114069054A

  • Liquid injection formation process of lithium ion battery and lithium ion battery

    CN114300818A